EFFECTIVENESS OF USING INTERACTIVE METHODS IN TEACHING NATURAL SCIENCES IN PRIMARY CLASSES - Atayeva Bakhrinisa Abduvakhidovna (American Journals, 2023)
In this article, focusing on the goals of teaching natural sciences in elementary grades and the possibilities of using interactive methods in their effective organization, the methods of "Organizer", "Tour through the gallery", "3X2", "Creative work" are discussed in the lesson. ways to stay are indicated.
Keywords: natural science, national program, interactive methods